PENGETAHUAN, SIKAP DAN PERILAKU MASYARAKAT TENTANG PENYAKIT TUBERKULOSIS (TB) PARU DI KECAMATAN SUNGAI TARAB, KABUPATEN TANAH DATAR PROPINSI SUMATERA BARAT - Media, Yulfira (Media Penelitian dan Pengembangan Kesehatan, 2011)
Tuberculosis (TB) Paru is still one of the major health problems in West Sumatera. Many efforts has been conducted to outcome the problem, one of them  is the DOTS strategy. The survey of community knowledge, attitude and behaviour related to tuberkulosis Paru was conducted in Sungai Tarab subdistrict, Tanah Datar Regency in 2010. The survey aims to explore community knowledge, attitude and behaviour as well as their effort to prevent the disease the survey was designed was as a qualitative study, in which data collection was done through indepth interview and Focus Group Discussion (FGD) with several informants such community leaders,patients, traditional health provider, and caders. The  results showed that most of informant have known the TB symptons well, but some of them still believe the disease is related to magic or genetic factor. Half informants also think  that  the TB symptom are usual, so that the specific treatment is not needed. This perception makes them do not seek helpl for health services. The TB pacients fell ashame to do regular spuktum check  to health centre because the do not want other people know that they suffered from TB.